Regulation of aortic carboxypeptidase-like protein (ACLP) during 3T3-L1 adipogenesis. - Abaiian, Kayvan Jasper. (University of Ottawa (Canada), 2001)
The 175 kD aortic carboxypeptidase-like protein (ACLP), suggested to be involved in smooth vascular muscle cell differentiation, has been shown to be expressed in 3T3-L1 preadipocytes. In this study we demonstrate that ACLP protein expression is transiently but significantly down-regulated by day 2 of an 8-day 3T3-L1 differentiation. ACLP protein down-regulation correlates with increases in cell number, suggesting a potential link between ACLP and clonal expansion. The transient modulation of ACLP is shown to be partly due to transcriptional regulation. Analysis of the individual components of differentiation cocktail indicate that all components are necessary to induce maximal ACLP downregulation and, as such, this event is differentiation-dependent. Although ACLP overexpression had no apparent effect on adipogenesis, its pattern of expression, unique to post-mitotic proliferation, indicates a potential role for ACLP in adipose tissue development and warrants further investigation to elucidate its function during preadipocyte differentiation.
Keywords: Biology, Cell.